The Leaching of Iron and Loss of Phosphate in Acid Sulphate Soil Due to Rice Straw and Phosphate Fertilizer Application - Arifin Fahmi; Bostang Radjagukguk; Benito Heru Purwanto (UNIVERSITY OF LAMPUNG, 2012)
Low phosphorus (P) availability and high iron (Fe) concentration are the dominant characteristics of acid sulphate soils (ASS). Optimum agricultural management practices are required to leach the excess Fe2+ and to prevent or minimize loss of P from the soil in order to obtain conditions favorable for rice growth. The aim of this experiment was to study the effect of organic matter (OM) application in the form of rice straw (RS) on leaching of Fe and loss of P in an acid sulphate soil. The experiment was conducted in the glasshouse consisting of three treatment factors utilizing the completely randomized design with three replications. The first factor was soil condition consisting of continuous application of RS and without RS during the past five years. The second factor was application of fresh RS consisting of fresh RS application and without fresh RS application, whereas the third factor was P application consisting of three rates of SP-36 fertilizer (0.5, 1.0 and 1.5 times of the recommended rate). The results showed that RS application was effective in preventing P loss from the soil at 6 weeks after planting (WAP) and decreased the pH of leachate at all observations time but it increased Fe2+ concentration in leachate (0.07-0.42% Fe2+ in the soil were leached or 2-5 folds higher than without RS application).